Comparative Assessment of Physico-Functional, Nutritional, and Antioxidant Properties of Yam Flours From Southern Sri Lanka - Manikka Badathuruge Lahiru Gayan De Silva; Wijesundara Weerarathna Himansha Navodi; Ganwarige Sumali Nivanthi Fernando; Perumpuli Arachchige Buddhika Niroshie Perumpuli (Food ScienTech Journal, 2026)
Yams (Dioscorea spp.) are traditional starchy root crops grown mainly by small-scale farmers in Sri Lanka and valued for their rich content of fiber, vitamins, and minerals. This study aims to fill the gap by characterizing the physico-functional, nutritional, and antioxidant properties of selected yam flours cultivated in the Southern Province and evaluating their potential in value-added food applications. The purpose of this study was to compare six locally accessible yam varieties which are Arrowroot, Kiri ala, Buthsarana, Kahata ala, Dandila White, and Dandila Purple, with commercially available wheat and rice flours in order to assess their physico-functional, nutritional, and antioxidant qualities. The physico-functional properties were analysed by using standard methods. Proximate composition of flour types was analyzed using standard AOAC methods. Yam flours showed bulk densities that were in close contact with those of wheat and rice flours. Different thermal qualities were suggested by the gelatinization temperatures. Dandila White demonstrated exceptional antioxidant potential. The findings offer novel evidence supporting yams as sustainable, health-enhancing substitutes in food formulations.